Smart Cameras - Belbachir, Ahmed Nabil; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2010)
Smart Cameras Edited by: Ahmed Nabil Belbachir Although there are many "definitions" of smart cameras offered by the media, camera manufacturers and developers, still no binding definition exists. For the purpose of this book, a smart camera is defined as a vision system which, in addition to image capture circuitry, is capable of extracting application-specific information from the captured images, along with generating event descriptions or making decisions that are used in an intelligent and automated system. This book provides a single-source reference, with content from several disparate scientific, technological and commercial aspects related to smart cameras: photoreceptors, pixels, signal processing, image sensor architectures, embedded systems, computer vision, sensor networks, applications of smart cameras and market trends. It provides background information, fundamentals, and an overview of the historical evolution, applications and the latest trends in intelligent camera concepts for professionals, researchers and practitioners. Provides information on smart cameras for an interdisciplinary audience (embedded systems; image processing; camera technology) of professionals, practitioners and students; Integrates coverage of hardware electronics, signal processing, embedded computing, computer vision, sensor networks and smart camera applications in surveillance, machine vision and the automotive industry; Includes an analysis of the smart camera market evolution, based on interviews with market leaders.
I INTRODUCTION TO SMART CAMERAS -- Smart Cameras: A Historical Evolution -- Smart Cameras: Fundamentals and Classification -- Smart Cameras: Technologies and Applications -- II IMAGING TECHNOLOGIES AND ARCHITECTURE OF SMART CAMERAS -- Detectors, Pixels, and Signal Processing -- Image Sensor Architectures -- III EMBEDDED VISION -- Embedded Vision Challenges -- High-Performance Smart Cameras -- Embedded Stereo Vision -- IV COMPUTER VISION FOR SMART CAMERAS -- Self-Calibrating Cameras in Video Surveillance -- Change Detection for Object Segmentation -- Object Tracking on Embedded Hardware -- V DISTRIBUTED SMART CAMERAS -- Designing a Wireless Smart Camera with a High-Performance Vision System -- Automatic Geo-registration and Inter-Sensor Calibration in Large Sensor Networks -- Application Development and Management of Smart Camera Networks -- Stereo Vision in a Network of Co-operative Cameras -- VI SELECTED APPLICATIONS OF SMART CAMERAS -- Smart Cameras for Machine Vision -- Smart Cameras for Visual Surveillance -- Camera-Based Automotive Systems -- VII SMART CAMERAS MARKETS -- Market Demands and Analysis -- VIII THE FUTURE OF SMART CAMERAS -- Future Directions of Smart Cameras.
Keywords: Signal processing; Image processing; Speech processing systems; Electronic circuits; Optical data processing; Signal, Image and Speech Processing; Circuits and Systems; Computer Imaging, Vision, Pattern Recognition and Graphics